Interaction of Mycobacterium leprae with the HaCaT human keratinocyte cell line: new frontiers in the cellular immunology of leprosy. Issue 7 (4th May 2015) - Lyrio, Eloah C.D.; Campos‐Souza, Ivy C.; Corrêa, Luiz C.D.; Lechuga, Guilherme C.; Verícimo, Maurício; Castro, Helena C.; Bourguignon, Saulo C.; Côrte‐Real, Suzana; Ratcliffe, Norman; Declercq, Wim; Santos, Dilvani O.
Abstract Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae affecting the skin and peripheral nerves. Despite M. leprae invasion of the skin and keratinocytes importance in innate immunity, the interaction of these cells in vitro during M. leprae infection is poorly understood. Conventional and fluorescence optical microscopy, transmission electronic microscopy, flow cytometry and ELISA were used to study the in vitro interaction of M. leprae with the HaCaT human keratinocyte cell line. Keratinocytes uptake of M. leprae is described, and modulation of the surface expression of CD80 and CD209, cathelicidin expression and TNF‐α and IL‐1β production of human keratinocytes are compared with dendritic cells and macrophages during M. leprae interaction. This study demonstrated that M. leprae interaction with human keratinocytes enhanced expression of cathelicidin and greatly increased TNF‐α production. The highest spontaneous expression of cathelicidin was by dendritic cells which are less susceptible to M. leprae infection. In contrast, keratinocytes displayed low spontaneous cathelicidin expression and were more susceptible to M. leprae infection than dendritic cells. The results show, for the first time, an active role for keratinocytes during infection by irradiated whole cells of M. leprae and the effect of vitamin D on this process. They also suggest that therapies which target cathelicidin modulation may provide novel approaches for treatment of leprosy.